Eefects Of Occupational Strain Among Police Officers To The General Security Of A Community: A Case Of Murang’a Town, Murang’a County, Kenya. - Kimotho, Felix; Mwangi, Wokabi; Omboto, John (Advances in Social Sciences Research Journal, 2018)
Strain at work in any profession negatively affects the people working and overall performance of employees. This in turn has a negative impact on production or quality of services being offered. This applies to police officers especially those working in major towns in Kenya where crime rate is too high and cost of living is unimaginably high. According to GOK crime report of 2014, Murang’a town being one of the Kenyan major towns has been rated as having highest crime levels culminated by illegal groupings like Mungiki and Gaza boys. Among the major crimes recorded in Murang’a include violent robberies, theft of motor vehicles, house breakings and burglary, kidnapping, bank robberies, homicides and gender violence among others. Reasons behind high crime rate in Murang’a town have not been clearly established so far. Many scholars have tried to establish causes of crime in Murang’a town and among the listed causes include poverty levels, population growth and proximity to Kenyan capital Nairobi among others but none has considered effects of occupational strain among police officers in the course of performance of their duties. Occupational strain among police officers could be having adverse effects on performance by police officers and in turn negatively affect services they render to the public and this may lead to high crime rate and general insecurity. Failure to address causes of occupational strain among police undermines effort to curb insecurity in our major towns in Kenya. Strained officers are poorly motivated and generally demoralized hence poor service delivery. The focus of this paper, therefore, is to build greater understanding of the causes of occupational strain among police officers in Murang’a town, effects of such strain to general security of Murang’a town and possible measures that can be undertaken to address the problem of occupational strain among police officers working in Murang’a town. The paper briefly presents findings of research conducted in Murang’a town over the same topic and recommendations thereto, in order to address the problem of occupational strain among police officers and improve their welfare and wellbeing. All this is aimed at motivating them to provide good services and to make them more effective which in turn will improve security of Murang’a town.